Manuel Zapata Olivella: Illiterate lawyer (2021)
This essay pretends to show literature as an essential way used by Manuel Zapata Olivella, who writes his own experiences, according to his adventurous soul, and complaints about Afro-Colombian's culture oppression; taking into account our multi-ethnic inheritance and the different nations he visits, especially, Central America and Africa.